IMPLEMENTATION OF THE PROSPECTIVE BRIDE AND GROOM COURSE: A STUDY AT THE OFFICE OF RELIGIOUS AFFAIRS OF NORTH TIDORE DISTRICT - Abu, Asnawi; Abubakar, Fatum; Husein, Muhammad Ar. (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2025)
The Prospective Bride and Groom Course Program (SUSCATIN) for prospective husbands and wives by the government through the Ministry of Religion which is implemented by the KUA with the belief that the implementation of this program will create a harmonious family, Sakinah, Mawaddah and Warahmah.The method used in this study is a qualitative method. The purpose is to implement the Prospective Bride and Groom Course at the KUA of North Tidore District, Tidore Islands City. The formulation of the problem is How is the Implementation of SUSCATIN at the KUA of North Tidore? What are the opportunities and obstacles to the Implementation of the Prospective Bride and Groom Course at the KUA of North Tidore District, Tidore Islands City?. The results obtained are: 1) SUSCATIN at the KUA of North Tidore District has been implemented, but its implementation has not been optimal, due to several factors: a) there is no strong commitment from the Head of KUA and related staff, b) lack of resource persons, c) lack of supporting facilities, d) no budget/implementation costs prepared by the institution, and e) community tradition that does not allow prospective brides and grooms to leave the house several days before the implementation. 2) A number of opportunities and obstacles in the implementation of SUSCATIN at the KUA of North Tidore District, namely the weakness in the regulatory aspects that govern its implementation, including the absence of legal sanctions against prospective brides and grooms who do not participate in SUSCATIN and officers at the KUA who do not organize it, and SUSCATIN has not been made an absolute requirement in the marriage process, meaning it has not been placed as part of a basic requirement for the marriage process, so it does not have legal binding force